2017
DOI: 10.1159/000481558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liuweibuqi Capsules in Pulmonary Alveolar Epithelial Cells and COPD Through JAK/STAT Pathway

Abstract: Background/Aims: To evaluate the effect of Liuweibuqi capsules on chronic obstructive pulmonary disease (COPD) through the JAK/STAT pathway. Methods: Lung function was measured with a spirometer. Changes in lung histology were observed using H&E staining. Cigarette smoke extract combined with lipopolysaccharide (CSE+LPS) was used to establish the cellular COPD model. Cytokine levels were determined using ELISA, and changes in the JAK/STAT pathway were evaluated using western blotting. The CCK8 method and flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“… 67 Furthermore, the JAK2/STAT3 signaling pathway has been shown to play an important regulatory role in microglial reactivity to various stimuli and mediates proinflammatory responses in microglia in response to various insults. 73 75 In the present study, in early-stage DNP in STZ-induced DNP rats, the increased expression of IL-6 and JAK2/STAT3 in the dorsal spinal cord could be significantly suppressed by MRS2211. Dominguez et al suggested that intrathecal injection of anti-rat IL-6 antibodies obviously prevented SNL-induced accumulation of phospho-STAT3 in dorsal spinal cord microglia.…”
Section: Discussionsupporting
confidence: 46%
“… 67 Furthermore, the JAK2/STAT3 signaling pathway has been shown to play an important regulatory role in microglial reactivity to various stimuli and mediates proinflammatory responses in microglia in response to various insults. 73 75 In the present study, in early-stage DNP in STZ-induced DNP rats, the increased expression of IL-6 and JAK2/STAT3 in the dorsal spinal cord could be significantly suppressed by MRS2211. Dominguez et al suggested that intrathecal injection of anti-rat IL-6 antibodies obviously prevented SNL-induced accumulation of phospho-STAT3 in dorsal spinal cord microglia.…”
Section: Discussionsupporting
confidence: 46%
“…COPD is characterized by presence of progressive and poorly reversible airflow limitation and linked to abnormal inflammatory response to harmful particles or gases in the airways and the lungs [ 2 ]. It is reported that multiple processes such as inflammation, cellular apoptosis, oxidative stress, and abnormal cellular repair are involved in the pathogenesis of COPD [ 3 ]. AECOPD is a serious event that is responsible for the progress of the disease and thus increased mortality [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced pulmonary inflam-(�8,�9). Reduced pulmonary inflammation may therefore contribute to the recovery from lung injury (40,41).…”
Section: Discussionmentioning
confidence: 99%